Two Transcutaneous Stimulation Techniques in Shoulder Pain: Transcutaneous Pulsed Radiofrequency (TPRF) versus Transcutaneous Electrical Nerve Stimulation (TENS): A Comparative Pilot Study. (4th February 2019) - Lin, Mu-Lien; Chiu, Hung-Wei; Shih, Zao-Ming; Lee, Po-Ying; Li, Pei-Zhi; Guo, Chin-Hong; Luo, Yuan-Jie; Lin, Shen-Chieh; Lin, Kwan-Yu; Hsu, Yu-Ming; Pang, Angela; Pang, Weiwu
Abstract : Objective . To compare the safety and efficacy of 2 transcutaneous stimulation techniques, transcutaneous pulsed radiofrequency (TPRF) versus transcutaneous electrical nerve stimulation (TENS), in chronic shoulder tendonitis. Design . A prospective, randomized, and double-blind clinical trial. Setting . Academic pain service of a city hospital. Subjects . Fifty patients with sonography-confirmed shoulder tendonitis. Methods . Fifty patients were randomly allocated into two groups for electrical stimulation treatment with 3-month follow-ups: Group 1n = 25, TENS and Group 2n = 25, TPRF. Both groups underwent either treatment for 15 minutes every other day, three times total. Our primary goals were to find any treatment comfort level, adverse event, and changes in Constant–Murley shoulder (CMS) scores. The secondary goals were finding the changes in pain, enjoyment of life, and general activity (PEG) scores. Results . For primary goals, no adverse events were noted throughout this study. No differences were found between groups for treatment tolerability (3.20 + 0.87 vs. 2.16 + 0.75). Statistically significant lower PEG scores were noticeable with the TPRF group after the course (12.73 + 5.79 vs. 24.53 + 10.21, p = 0.013 ). Their statistical significance lasted for 3 months although the difference gap diminished after 1 month. CMS scores were significantly higher in the TPRF group (70.84 + 6.74 vs. 59.56 + 9.49, p = 0.007 ) right after treatment course but the significance did not last. Conclusions . In treating chronic shoulder tendinitis using two transcutaneous stimulation techniques, both TPRF and TENS are safe and effective. TPRF is superior to TENS.